Mevastatin-Induced AP-1-Dependent HO-1 Expression Suppresses Vascular Cell Adhesion Molecule-1 Expression and Monocyte Adhesion on Human Pulmonary Alveolar Epithelial Cells Challenged with TNF-α - Yang, Chuen-Mao (Biomolecules, 2020)
Mevastatin (MVS) has been previously shown to induce heme oxygenase (HO)-1 expression through Nox/ROS-dependent PDGFRα/PI3K/Akt/Nrf2/ARE axis in human pulmonary alveolar epithelial cells (HPAEpiCs). However, alternative signaling pathways might involve in MVS-induced HO-1 expression. We found that tumor necrosis factor α (TNFα) induced vascular cell adhesion protein 1 (VCAM-1) expression and NF-κB p65 phosphorylation which were attenuated by pretreatment with MVS via up-regulation of HO-1, determined by Western blot and real-time qPCR. TNFα-induced VCAM-1 expression was attenuated by an NF-κB inhibitor, Bay117082. The inhibitory effects of MVS were reversed by tin protoporphyrin (SnPP)IX (an inhibitor of HO-1 activity). In addition, pretreatment with the inhibitor of pan-Protein kinase C (PKC) (GF109203X), PKCα (Gö6983), Pyk2 (PF431396), p38α MAPK (SB202190), JNK1/2 (SP600125), or AP-1 (Tanshinone IIA), and transfection with their respective siRNAs abolished MVS-induced HO-1 expression in HPAEpiCs. c-Jun (one of AP-1 subunits) was activated by PKCα, Pyk2, p38α MAPK, and JNK1/2, which turned on the transcription of the homx1 gene. The interaction between c-Jun and HO-1 promoter was confirmed by a chromatin immunoprecipitation (ChIP) assay, which was attenuated by these pharmacological inhibitors. These results suggested that MVS induces AP-1/HO-1 expression via PKCα/Pyk2/p38α MAPK- or JNK1/2-dependent c-Jun activation, which further binds with AP-1-binding site on HO-1 promoter and suppresses the TNFα-mediated inflammatory responses in HPAEpiCs. Thus, upregulation of the AP-1/HO-1 system by MVS exerts a potentially therapeutic strategy to protect against pulmonary inflammation.